Effects of carbon dioxide insufflation in balloon-assisted enteroscopy: A systematic review and meta-analysis. Issue 1 (February 2016) - Nishizawa, Toshihiro; Suzuki, Hidekazu; Fujimoto, Ai; Ochiai, Yasutoshi; Kanai, Takanori; Naohisa, Yahagi
Background and aim: The efficacy of CO2 insufflation during balloon-assisted enteroscopy remains controversial. This study aimed to perform a systematic review with meta-analysis of randomized controlled trials (RCTs) in which CO2 insufflation was compared with air insufflation in balloon-assisted enteroscopy. Methods: PubMed, the Cochrane library, and the Igaku-Chuo-Zasshi database were searched to identify RCTs eligible for inclusion in the systematic review. Data from the eligible studies were combined to calculate the pooled odds ratios (ORs) or weighted mean differences (WMDs) with 95% confidence intervals (CIs). Results: Four RCTs (461 patients) were identified. Compared with air insufflation, CO2 insufflation significantly increased intubation depth of oral enteroscopy (WMD: 55.2, 95% CI: 10.77–99.65, p = 0.015). However, there was significant heterogeneity. The intubation depth of anal enteroscopy showed no significant difference between the CO2 group and the air group. CO2 insufflation significantly reduced abdominal pain compared with air insufflation (WMD: −2.463, 95% CI: −4.452 to −0.474, p = 0.015), without significant heterogeneity. The PaCO2 or end-tidal CO2 level showed no significant difference between the CO2 group and air group. Conclusions: Compared with air insufflation, CO2 insufflation during balloon-assisted enteroscopy caused less post-procedural pain without CO2 retention.